High-resolution records of sulfur and insoluble particle concentrations from the B19 ice core in Greenland between 1530 and 1710 CE - Sigl, Michael; McConnell, Joseph R; Chellman, Nathan J; Gabriel, Imogen (In: Sigl, M et al. (2025): High time resolution records of sulfur and insoluble particle concentrations from five ice cores from Greenland and one from Antarctica between 1530 and 1710 CE and inferred volcanic contributions [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974177, 2025)
We report high resolution (1 cm depth) sulfur concentrations from the B19 ice core in Greenland analyzed using inductively coupled plasma mass spectrometry (ICPMS) and mass concentrations of insoluble particles (5-10um size) using an inline Abakus® laser particle counter at the Desert Research Institute. Details about the analytical procedures are provided in the references. These records are used alongside ice-core crypto-tephra to characterize volcanic eruption sources in the 1660s CE.
Keywords: Antarctica; Cryptotephra; Greenland; Ice core; Long Island; particle mass concentration; sulfate; sulfate aerosol; Sulfur; Tarumae; Tephra; volcanic forcing